Fatigue Sensitivity Analysis of Offshore Fixed Platform Structure in The Natuna Sea - Nafisa Nandalianadhira; Mochammad Fathurridho Hermanto; Aqsha Khaylla Riquelle; Andreas Owen Hotman Nainggolan (Universitas Trunodjoyo Madura, 2026)
Offshore fixed platform is one of the various types of platforms that are very suitable to be built in water areas with not too deep depths such as the Natuna Sea Waters area. This study analyzes fatigue in an offshore fixed platform in the Natuna Sea (309 ft depth), a region suitable for such structures due to its relatively shallow waters. The platform, with its tubular joints, is susceptible to fatigue from cyclical wave loads, particularly in the braces. The research employed in-place and fatigue analyses, using a deterministic method and adhering to API RP 2A-LRFD standards. In-place analysis revealed peak unity check values of 0.95 for the Pile (P1C) during operation and 0.96 for the Conductor (CO3) during storms. Maximum deflections were recorded: 14.728 inches horizontally at joint H005, and -3.339 inches vertically at joint C064. Fatigue analysis indicated a minimum service life of 73.40 years at joint 303L, located in the splash zone, where wave influence remains significant. Sensitivity analysis highlighted the crucial role of brace gap and chord thickness in determining service life. Increased brace gap negatively impacts service life, while chord thickness significantly influences it. This research provides critical insights for ensuring the structural integrity and longevity of offshore fixed platforms in similar environments.